HUBUNGAN ANTARA UMUR, BOBOT BADAN DAN PRODUKSI SUSU SAPI PERAH FRIESIAN HOLSEIN - Umbang Arif Rokhayati; Sri Yenny Pateda (xxxx-xxxx, 2022)
Body weight in livestock, especially dairy cows greatly affects milk production, therefore the delay in providing adequate feed will also affect milk production. Therefore, the relationship between body weight and milk production in Friesian Holstein dairy cows is very closely related. This study aims to examine the relationship between body weight and milk production in Friesian Holstein dairy cows. While the material used is dairy cows that are lactating aged between 2-8 years (lactation age between 2-8 weeks) with a body weight between 400-600kg totaling 60 heads. In this study, the feed used was uniform consisting of forage and concentrate. Meanwhile, the observed variables were the age of the cattle, the lactation period and the milk produced, then the data obtained were tested descriptively. The results of this study showed that Friesian Holstein dairy cows experienced peak production at the fourth lactation, aged 5-6 years, body weight between 551-650 kg, milk production averaged 89.70 head/liter/day